2018
DOI: 10.1016/j.molcel.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mapping of Histone Modifications at DNA Double-Strand Breaks Deciphers Repair Pathway Chromatin Signatures

Abstract: SummaryDouble-strand breaks (DSBs) are extremely detrimental DNA lesions that can lead to cancer-driving mutations and translocations. Non-homologous end joining (NHEJ) and homologous recombination (HR) represent the two main repair pathways operating in the context of chromatin to ensure genome stability. Despite extensive efforts, our knowledge of DSB-induced chromatin still remains fragmented. Here, we describe the distribution of 20 chromatin features at multiple DSBs spread throughout the human genome usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
285
6
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(342 citation statements)
references
References 74 publications
(119 reference statements)
26
285
6
5
Order By: Relevance
“…Two studies, which also observe an increase in H3K36me2 at DSB sites, linked this increase to the removal of histone demethylases from the chromatin rather than active methylation (19, 20). In contrast, a recent study did not found any increase in H3K36me2 at a DSB site but found instead an increase in H3K36me3 (21). We recently found that SETMAR N210A mutant was decreasing the bulk level of H3K36me2 by western blot and also observed a decrease of H3K36me3 at some genomic positions, possibly because of a decreased H3K36me2 level which is required by SETD2 for adding the third methyl group (7).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Two studies, which also observe an increase in H3K36me2 at DSB sites, linked this increase to the removal of histone demethylases from the chromatin rather than active methylation (19, 20). In contrast, a recent study did not found any increase in H3K36me2 at a DSB site but found instead an increase in H3K36me3 (21). We recently found that SETMAR N210A mutant was decreasing the bulk level of H3K36me2 by western blot and also observed a decrease of H3K36me3 at some genomic positions, possibly because of a decreased H3K36me2 level which is required by SETD2 for adding the third methyl group (7).…”
Section: Discussioncontrasting
confidence: 56%
“…Two other papers linked the increase in H3K36me2 following DSBs to the inhibition of KDM2A and KDM2B, two histone demethylases involved in the removal of H3K36 methylation (19, 20). However, a recent study did not observe an increase in H3K36me2 around DSB sites (21).…”
Section: Introductionmentioning
confidence: 93%
“…Several chromatin remodelers and modifiers that affect the relative activity of the various DNA repair pathways have been identified, which demonstrated that the correct chromatin conformation in proximity to a DSB is critical to ensure successful DNA repair 25 . These findings have sparked an interest in the role of native chromatin on DNA repair pathway choice [26][27][28] . However, studying the effects of chromatin context on repair pathway choice is not straightforward when using common agents to induce DSBs, such as -irradiation or DNA damaging chemotherapeutics 29 .…”
Section: Introductionmentioning
confidence: 99%
“…This pattern differs from the replication pattern observed for other known instances of genome re-replication during embryonic development 43 , when cells undergo numerous iterations of entire genome duplication, with S phases and M phases alternating to re-license origins anew after the completion of each replication cycle. Because re-replicated DNA can be more susceptible to damage and breakage, the preferential re-replication of early-replicated DNA can be linked to the observed clustering of DNA breaks in euchromatic regions 53,54 .…”
Section: Discussionmentioning
confidence: 99%